Konsep Pembelajaran Kontekstual Bahasa Indonesia Berbasis Sastra Pariwisata pada Destinasi Sejarah Kabupaten Mojokerto - Zainudin, Moh. (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
Indonesian language learning extends beyond linguistic proficiency, serving a strategic role in instilling cultural values, historical awareness, and local wisdom. This article conceptually explores the integration of literary tourism into contextual-based Indonesian language instruction, highlighting the historical destinations of Mojokerto Regency as learning resources. Such an approach is believed to strengthen students’ literacy competence while simultaneously fostering awareness of cultural heritage. Drawing upon constructivist theory, the framework of literary tourism texts, and the application of local contexts in learning, the study proposes a conceptual model and development scheme applicable to both secondary and higher education levels. The findings suggest that contextualizing Indonesian language learning through literary tourism not only enriches students’ engagement with language and literature but also positions education as a medium for cultural preservation. The article concludes that integrating literary tourism into the curriculum represents a relevant and innovative strategy to bridge linguistic skills with cultural and historical consciousness.